Tian-ren-he-yi strategy: An Eastern perspective - Peng, Mike; Li, Y.; Tian, L. (Springer New York LLC, 2016)
Research on the business-environment dilemma has traditionally focused on strategies based on isolated, either/or mindsets, such as economically-oriented and environmentally-oriented strategies. Drawing on the cultural, philosophical, and intellectual traditions of China, we sketch the contours of a new holism-based strategic mindset, which results in a tian-ren-he-yi strategy. As an Eastern perspective, tian-ren-he-yi means “nature and mankind combined as one” or “nature-human harmony.” We leverage both qualitative and quantitative investigations to first identify the underlying mechanisms connecting tian-ren-he-yi strategy and firm performance, and then to compare the performance-enhancing potential of tian-ren-he-yi strategy with the two strategies based on the isolated mindset. Our analysis shows that when managing the business-environment dilemma, tian-ren-he-yi strategy has stronger performance-enhancing potential than either economically-oriented or environmentally-oriented strategies.